Explicating Abjection – Historically White Universities creating Natives of Nowhere? - Kumalo, Siseko Hudson (Critical Studies in Teaching and Learning, 2023)
In Ebrahim Patel’s, the world of Nat Nakasa: A collection of letters, Nathaniel Nakasa’s term ‘Native of Nowhere’ describes Nakasa’s experience of leaving South Africa on an exit permit. Negotiating his classification as an aggressor of the state, Nakasa’s expression signals his confrontation with his expendability as a Native in a country founded on the use of Blackness as Blackbodies that prop up white supremacy and rule. ‘Native of Nowhere’ here details how historically white universities in South Africa perpetuate ontological negations, through denying Blackness in institutions formerly reserved for whiteness. Through an analysis that implicitly posits education as a public good, I argue for the use of education as an emancipatory tool. Using Jean-Paul Sartre’s Being and No thing ness to analyse negation, I develop the ‘Native of Nowhere’ to articulate a critical pedagogy, which delivers on the emancipatory potential of education.